Electrical energy generation from piezoelectric materials - Lau Lee Tak (School of Electrical System Engineering, University Malaysia Perlis, 2011)
The goal of this project is to harvest electrical energy from vibrating structures by using the piezoelectric materials. Definitive is developed, theoretical models to predict the output voltage which is generated from vibrating piezoelectric materials attached to a cantilever beam. The predictive models are validated by comparing them to experimental data. The results show that the Euler-Bernoulli model must appropriately represent the piezoelectric material. Besides, parametric optimization for the cantilever beam systems power generation capability is discussed. The alternating voltage generated by the piezoelectric material is rectified and then stored in a nickel metal hydride battery. The project proves that small power harvesting from piezoelectric materials is possible and this provides a new alternative in electrical energy generation.